Wafer‐scale GaN HEMT performance enhancement by diamond substrate integration. Issue 3 (7th February 2014) - Via, G. D.; Felbinger, J. G.; Blevins, J.; Chabak, K.; Jessen, G.; Gillespie, J.; Fitch, R.; Crespo, A.; Sutherlin, K.; Poling, B.; Tetlak, S.; Gilbert, R.; et al.
Abstract: A wafer‐scale comparison of HEMTs fabricated on as‐grown GaN/Si and HEMTs fabricated in parallel on epitaxial layers from the GaN/Si growth integrated with a diamond substrate are presented. Diamond, which offers the highest room‐temperature thermal conductivity of any bulk material, is being evaluated as a solution for thermal limitations observed in GaN‐based devices. This paper will present electrical and thermal data collected at the wafer scale demonstrating the improvement realized by integration of a high‐thermal‐conductivity substrate. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)